Character Education Values Of Batik Tulis At Widya Batik Ubud, Bali - Nyoman Astawan; Ni Kadek Mia Indra Dewi (Journal of Sustainable Development Science, 2022)
This study aims to determine the values ​​of character education implicit in Batik Tulis at Widya Batik Ubud, Bali. There are two Batik studied, namely the work entitled Bunga Lotus and Mandala Yoga. The method used in this research is qualitative. Data collection methods used are documents, interviews, and observations. While the data collection techniques used are the card and note technique. And the data analysis methods used include data identification, data reduction, data presentation and processing, and concluding. Based on the results of data analysis, it can be concluded that there are four values ​​of character education of Batik Tulis at Widya Batik Ubud, Bali, namely religious values, environmental care values, creative values, and peace-loving values.